The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1103/physrevapplied.13.034036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heat Transfer with Metal-Dielectric Core-Shell Nanoparticles

Abstract: Heat transfer from irradiated metallic nanoparticles is relevant to a broad array of applications ranging from water desalination to photoacoustics. The efficacy of such processes relies on the ability of these nanoparticles to absorb the pulsed illuminating light and to quickly transfer energy to the environment. Here we show that compared to homogeneous gold nanoparticles having the same size, gold-silica core-shell nanoparticles enable heat transfers to liquid water that are faster. We reach this conclusion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 87 publications
(130 reference statements)
1
22
0
Order By: Relevance
“…This interpretation is, at least qualitatively, consistent with time-resolved spectroscopy experiments demonstrating faster heat transfer for gold nanoparticles coated with thin silica shells and immersed in water as compared with bare gold nanoparticles [23]. Faster heat transfer is also found in two-temperature model simulations of heat transfer across gold nanoparticles embedded in very thin silica shell [24]. Facilitated heat transfer is, in this case, ascribed to electron-phonon processes taking place at the interface between gold and the silica shell.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…This interpretation is, at least qualitatively, consistent with time-resolved spectroscopy experiments demonstrating faster heat transfer for gold nanoparticles coated with thin silica shells and immersed in water as compared with bare gold nanoparticles [23]. Faster heat transfer is also found in two-temperature model simulations of heat transfer across gold nanoparticles embedded in very thin silica shell [24]. Facilitated heat transfer is, in this case, ascribed to electron-phonon processes taking place at the interface between gold and the silica shell.…”
Section: Introductionsupporting
confidence: 85%
“…1 and eq. 2, we have assumed uniform temperatures for both the electronic and metal phonon degrees of freedom, as we have already shown that heat diffusion inside the metal core has little effect on the nanoparticle thermal relaxation following the laser excitation [24].…”
Section: A Nanoparticlementioning
confidence: 99%
See 2 more Smart Citations
“…Such attention to core-shell nanoparticles arises from the fact that they can exhibit enhanced physical and/or chemical properties. [1][2][3] Furthermore, core-shell particles with distinctly new properties compared to those of the constituent materials can be designed by tuning, for example, their size, shell thickness, and structures. [4][5][6][7] A large number of research projects are underway to fabricate highly functional core-shell materials for applications in various elds, including optoelectronic devices, 8,9 biomedical imaging, 10,11 catalysis, 12,13 and plasmonics.…”
Section: Introductionmentioning
confidence: 99%